The use of a novel toe–thumb pressure index for assessing arterial status in the lower limb. A reliability and validity study - Juliana Mazzeo; Helen A. Banwell; Peta E. Tehan; Grace Anderson; Kristin Graham (Journal of Foot and Ankle Research)
Abstract Aims This study explored the reliability, validity and perceived comfort of a novel thumb pressure measure and calculation of a toe–thumb index to identify their suitability as an adjunct or alternatives to ankle–brachial and toe–brachial indices. Methods and Results Repeated manual thumb and toe systolic blood pressures were conducted using two raters, over two time points, on 34 healthy participants. Concurrent automated toe, thumb and brachial systolic blood pressures as well as comfort ratings for these measures (using a 10 mm visual analogue scale) were captured once by a research assistant. Automated thumb and brachial measures showed fair correlation (ρ = 0.36, p = 0.03) and a toe–thumb index and toe–brachial index good correlation (ρ = 0.62, p < 0.01). Intraclass correlation coefficients (ICC) identified moderate intra‐rater reliability for manual thumb pressures for Rater 1 and 2 (ICC 0.57, 95% CI [0.14, 0.79] and ICC 0.74, 95% CI [0.49, 0.87], respectively), while inter‐rater reliability was poor (ICC = 0.16, 95% CI [−0.85, 0.47]). Concurrent validity comparing manual and automated measures for thumb pressure was also poor (ICC −0.05, 95% CI [−1.06, 0.72] and ICC 0.42, 95% CI [−0.16, 0.72] Rater 1 and 2 respectively). Thumb measures were significantly more comfortable than brachial measures (5 mm, p < 0.00). Conclusion Thumb systolic pressures are correlated with brachial systolic pressures, with reasonable intra‐rater reliability, however, correlation is only fair and measurement error wider than clinically acceptable. Furthermore, manual measures are poorly correlated with automated units. Consequently, caution is required in applying these techniques. As thumb measures were perceived as significantly more comfortable than brachial measures and have an advantage where brachial pressures cannot, or should not, be obtained, further evaluation is warranted.